Vaginal versus caesarean delivery: an institutional experience from North India - Amin, Fiza; Tali, Tavseef Ahmad; Ara, Rifat; Amin, Huda (International Journal Of Community Medicine And Public Health, 2023)
Background: The purpose of this study was to recognise and evaluate the common maternal concerns that emerge following vaginal and caesarean deliveries. Methods: In this retrospective study, hospital records of 300 pregnant patients who delivered in our hospital between July 2021 to December 2021 were analysed. Results: In total of 300 patients, 110 had caesarean and 190 had vaginal delivery, 16 (14.5%) patients developed wound infection in caesarean and 6 (3.15%) in vaginal delivery, 12 patients developed post-partum haemorrhage after undergoing vaginal delivery and 6 patients after caesarean. There were 2 deaths reported in caesarean mode and only 1 in vaginal mode of delivery. Conclusions: The study's findings indicate that caesarean had greater rates of maternal problems than vaginal delivery did.